Hubungan Kepemimpinan Kepala Sekolah dan Profesionalisme Guru Terhadap Kompetensi Peserta Didik di SD Negeri 18 Tumampua I Kecamatan Pangkajene Kabupaten Pangkep - Syam, Herwan; Saripuddin, Saripuddin; W, Muhammad Fahreza (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
The research aims to determine 1) the relationship between the principal's leadership and student competency at SD Negeri 18 Tumampua I, Pangakajene District, Pangkep Regency, 2) the relationship between teacher professionalism and student competency at SD Negeri 18 Tumampua I, Pangakajene District, Pangkajene Regency, 3) the relationship between the principal's leadership and teacher professionalism on student competency at SD Negeri 18 Tumampua I, Pangakajene District, Pangkep Regency. Pangkep. The type of research used is quantitative research. The research location is SD Negeri 18 Tumampua I, Pangakajene District, Pangkep Regency. The population in this research is all students, where the sample is 62 students. The data analysis techniques used are research instrument testing, analytical prerequisite testing, descriptive analysis and correlation analysis. The results of the research show that 1) there is a relationship between principal leadership and student competency at SD Negeri 18 Tumampua I, Pangakajene District, Pangkep Regency based on a sig value of 0.020 0.05, 2) there is a relationship between teacher professionalism and student competency at SD Negeri 18 Tumampua I, Pangakajene District, Pangkep Regency based on a sig value of 0.031 0.05, 3) Student Competence and Teacher Professionalism have a "medium" relationship with Student Teacher Competency at Tumampua I Public Elementary School, Pangkajene District, Pangkep Regency.